Method for preparing manganese violet pigment by using waste zinc-manganese battery black powder and recycling phosphorus ammonium salt

CN122978748APending Publication Date: 2026-10-27BEIJING INST OF CLOTHING TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611279833.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-21
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0008]若直接将废锌锰电池黑粉、回收磷铵盐和磷酸进行普通搅拌或简单共同粉碎,再进行一次高温煅烧,通常面临以下问题:a.废电池富锰氧化物中MnO2、MnOOH、Mn2O3和无定形锰氧化物共存,不同物相的Mn-O键能、晶格稳定性和反应活性存在差异,普通混合条件下容易发生反应不均匀;b.回收磷铵盐中的镁、钙、铁、钠和钾等杂质可能形成独立磷酸盐杂相,降低锰紫物相纯度;c.一次高温煅烧容易导致水分和氨快速逸出、物料鼓泡、颗粒烧结和铵根损失,使NH4MnP2O7转化为不含铵的锰焦磷酸盐、锰偏磷酸盐或其他非目标物相

Benefits of technology

本发明采用两阶段机械化学处理,先完成锰氧化物与磷铵盐颗粒的界面压合和准冷焊式复合,再提高机械能输入构筑高活性前驱体,能够增大反应界面面积并缩短锰、磷组分的扩散距离;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978748A_ABST
    Figure CN122978748A_ABST
Patent Text Reader

Abstract

The application discloses a method for preparing manganese violet pigment by using waste zinc-manganese battery black powder and recycled phosphorus ammonium salt, and relates to the technical fields of resource utilization of waste batteries, recycling of secondary resources containing phosphorus and preparation of inorganic pigments. The method comprises the following steps: pretreating the waste zinc-manganese battery black powder and the recycled phosphorus ammonium salt respectively to obtain manganese oxide and acidified phosphorus ammonium composite material respectively; separately performing first mechanical chemical treatment on the manganese oxide to obtain defective manganese oxide; adding the acidified phosphorus ammonium composite material into the defective manganese oxide in batches, and performing second mechanical chemical treatment under dry material conditions to obtain a precursor; directly performing segmented heat treatment on the precursor, and finally performing washing and drying to obtain a manganese violet pigment product. The method combines two-stage mechanical chemical treatment with segmented low-temperature pyrophosphatization, reduces the crystallization temperature, improves the phase purity and ammonium retention rate of NH4MnP2O7, and realizes the synergistic high-value utilization of the waste zinc-manganese battery black powder and the recycled phosphorus ammonium salt.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the fields of waste battery resource utilization, phosphorus-containing secondary resource recycling, and inorganic pigment preparation technology. Specifically, it is a method for preparing manganese violet pigment using waste zinc-manganese battery black powder and recycled ammonium phosphate salt. Background Technology

[0002] With the widespread use of remote controls, toys, household appliances, instruments, emergency lighting equipment, and other portable electrical devices, carbon-zinc manganese batteries and alkaline zinc manganese batteries still have a large social inventory. After dismantling and sorting, waste zinc manganese batteries yield a black powder containing manganese oxide, zinc or zinc oxide, graphite, acetylene black, ammonium chloride, zinc chloride, potassium salts, and small amounts of iron, copper, and organic sealing materials, commonly known as waste zinc manganese battery black powder.

[0003] The manganese in waste zinc-manganese battery black powder has high resource utilization value. Its main phases can include MnO2, MnOOH, Mn2O3, Mn3O4, and amorphous manganese oxides. If waste zinc-manganese batteries are directly put into the municipal solid waste treatment system without proper treatment, it will not only waste manganese and zinc resources, but also the soluble salts, residual electrolytes, and metal impurities may pose potential environmental risks to soil and water bodies.

[0004] Manganese violet pigment, also known as manganese ammonium pyrophosphate pigment or pigment violet 16, has a main chemical composition of trivalent manganese ammonium pyrophosphate, with an approximate chemical formula of NH4MnP2O7. Manganese violet pigment possesses a vibrant range of reddish-purple to bluish-violet hues and exhibits good lightfastness, weather resistance, and pigment dispersion properties, making it suitable for use in artistic pigments, coatings, and ceramic decorative materials. Traditional manganese violet pigment is typically produced from commercial manganese dioxide, ammonium dihydrogen phosphate, and phosphoric acid through a mixture, heating for dehydration, and pyrophosphorylation reaction.

[0005] Existing technologies for recycling waste zinc-manganese batteries mainly include physical sorting, acid leaching, ammonia leaching, alkaline leaching, reductive leaching, oxidative roasting, and precipitation separation. Some existing technologies use ammoniacal ammonium carbonate solution to form zinc-ammonia complexes that enter the liquid phase, while most of the high-valence manganese oxides remain in the solid phase, thus achieving selective separation of zinc and manganese. This type of method can obtain a low-zinc, manganese-rich solid phase, but its main technical purpose is usually to recover zinc, prepare manganese dioxide, or provide manganese-rich raw materials for subsequent hydrometallurgical processes. It does not address the lattice formation, ammonium retention, pyrophosphate condensation, and pigment color stability of manganese violet pigment.

[0006] Chinese patent CN106241880A discloses a method and its uses for recovering high-purity manganese dioxide from waste manganese dry batteries. The method involves steps such as crushing and sorting, water washing, alcohol washing, alkali washing, acid washing, secondary water washing, and low-temperature oxygen-enriched roasting to remove soluble salts, organic matter, zinc salts, and carbonaceous impurities from the black powder, thereby obtaining the manganese dioxide product. Chinese patent CN104183856A discloses a method for recycling waste zinc-manganese batteries, recovering chemical raw materials from waste batteries through steps such as dismantling, ammonolysis, filtration, vacuum evaporation, and acid hydrolysis. While these methods can recover some components from waste zinc-manganese batteries, none disclose a technical route for preparing manganese violet pigment using multiphase manganese-rich oxides from waste batteries.

[0007] On the other hand, in wastewater treatment, anaerobic digestion, phosphate fertilizer production, and the treatment of phosphorus-containing industrial wastewater, phosphorus- and ammonium-containing recovered salts can be obtained through crystallization, evaporation concentration, and recrystallization. These recovered salts may contain ammonium dihydrogen phosphate, diammonium hydrogen phosphate, ammonium phosphate, and small amounts of magnesium, calcium, iron, sodium, potassium, and organic impurities. Currently, recovered phosphate and ammonium salts are mainly used in fertilizer or nutrient products, and are less commonly used in the preparation of inorganic pigments that require high stoichiometry, impurity content, crystal phase, and overall color.

[0008] If waste zinc-manganese battery black powder, recovered ammonium phosphate, and phosphoric acid are directly mixed or simply crushed together and then subjected to a high-temperature calcination, the following problems are usually encountered: a. In the manganese-rich oxides of waste batteries, MnO2, MnOOH, Mn2O3, and amorphous manganese oxides coexist. The Mn-O bond energies, lattice stability, and reactivity of different phases vary, and uneven reaction is likely to occur under ordinary mixing conditions; b. Impurities such as magnesium, calcium, iron, sodium, and potassium in the recovered ammonium phosphate may form independent phosphate impurity phases, reducing the purity of the manganese purple phase; c. A single high-temperature calcination can easily lead to the rapid escape of moisture and ammonia, material bubbling, particle sintering, and ammonium ion loss, causing NH4MnP2O7 to be converted into manganese pyrophosphate, manganese metaphosphate, or other non-target phases that do not contain ammonium.

[0009] Therefore, there is an urgent need to develop a mechanochemical treatment method that differs from ordinary ultrafine grinding. First, lattice distortion, oxygen vacancies, and low-coordinated manganese sites are constructed in manganese-rich oxides. Then, the defect sites are used to conduct mechanochemical interface pressing and quasi-cold welding coupling with acidified ammonium phosphate composites. The resulting manganese-phosphorus interface structure is then continuously connected with the subsequent low-temperature pyrophosphorylation process to obtain manganese violet pigment with uniform composition, good crystallinity, and stable overall color. Summary of the Invention

[0010] The purpose of this invention is to provide a method for preparing manganese violet pigment using waste zinc-manganese battery black powder and recycled ammonium phosphate. Instead of using selective zinc removal with ammoniacal ammonium carbonate as the core technology, this method uses zinc removal as a preferred pretreatment to obtain low-zinc, high-manganese oxides. The low-zinc, low-carbon, high-manganese oxides are first subjected to independent high-energy mechanochemical treatment, avoiding the buffering effect of pre-coating with ammonium phosphate on mechanical impact, thus causing lattice distortion, oxygen vacancies, and low-coordination manganese sites in the high-manganese oxides. Subsequently, acidified ammonium phosphate composites are added in batches to the defective high-manganese oxides. Through mechanical impact, shearing, compaction, and local viscoplastic flow, the acidified ammonium phosphate composites are embedded on the newly formed surface of the manganese oxides, forming a Mn-OP interface bond. The resulting mechanochemically coupled precursor is directly subjected to segmented low-temperature pyrophosphorylation without water washing and liquid-phase redispersion, thereby achieving uniform nucleation and crystal growth of NH4MnP2O7 at a lower temperature.

[0011] To achieve the above objectives, the present invention employs the following technical means: A method for preparing manganese violet pigment using waste zinc-manganese battery black powder and recycled ammonium phosphate salt includes the following steps: S1. Pre-treat the waste zinc-manganese battery black powder and the recovered ammonium phosphate salt separately to obtain a composite material of manganese-rich oxide and acidified ammonium phosphate; S2. The manganese-rich oxide is subjected to a first mechanochemical treatment alone to obtain a defective manganese-rich oxide; S3. The acidified ammonium phosphate composite is added to the defective manganese-rich oxide in batches, and a second mechanochemical treatment is carried out under the condition that the moisture content is not higher than 5 wt.% to obtain the manganese-phosphorus-ammonium mechanochemical coupling precursor. S4. The manganese-phosphorus-ammonium mechanochemical coupling precursor is directly subjected to segmented heat treatment, wherein the segmented heat treatment includes dehydration, interfacial polycondensation and crystallization in sequence to obtain crude manganese violet pigment product. S5. The crude manganese violet pigment product is washed and dried to obtain the manganese violet pigment product.

[0012] Preferably, the preprocessing in step S1 includes: The waste zinc-manganese battery black powder is subjected to desalination, decarbonization and dezincification treatment; Purification of the recovered ammonium phosphate salt and acidification reconstruction by adding phosphoric acid and / or recovering phosphoric acid.

[0013] Furthermore, the zinc removal process employs at least one of the following methods: ammonia complex leaching, alkaline leaching, selective acid leaching, or physical sorting.

[0014] Furthermore, the purification includes dissolution, filtration, adsorption, ion exchange, and / or recrystallization; the acidification and reconstruction adjusts the molar ratio of effective ammonium ions to manganese in the acidified ammonium phosphate composite to NH4+. 4+The ratio of total phosphorus to manganese (P:Mn) is 1.02 to 1.20:1, and the molar ratio of total phosphorus to manganese (P:Mn) is 1.95 to 2.15:1.

[0015] Furthermore, in step S2, the first mechanochemical treatment employs ball milling with a ball-to-material ratio of 8:1 to 15:1, a ball milling speed of 450 to 650 rpm, a ball milling time of 20 to 90 minutes, and a material temperature not exceeding 80°C.

[0016] Furthermore, the acidified ammonium phosphate composite material described in S3 is added in 2 to 5 batches, with each batch accounting for 20 to 50% of the total mass of the acidified ammonium phosphate composite material. After each batch is added, mechanical and chemical treatment is performed for 10 to 45 minutes, and after all batches are added, mechanical and chemical treatment is continued for 30 to 120 minutes.

[0017] Furthermore, the dehydration temperature in step S4 is 100~150℃, the interfacial condensation temperature is 190~240℃, and the crystallization temperature is 260~310℃.

[0018] Furthermore, the segmented heat treatment process is as follows: heating at 1~3℃ / min to 120~140℃ and holding for 30~90 minutes; heating at 0.5~2℃ / min to 210~235℃ and holding for 40~120 minutes; heating at 0.5~1.5℃ / min to 275~305℃ and holding for 60~240 minutes.

[0019] Furthermore, the washing described in step S5 uses phosphoric acid-acidified water with a pH of 2.5 to 4.5, and the washing includes a first-stage washing at 15 to 30°C and a second-stage washing at 35 to 55°C.

[0020] Furthermore, the drying described in step S5 is vacuum drying at 50~100°C.

[0021] The present invention has the following beneficial effects: This invention employs a two-stage mechanochemical process. First, it completes the interfacial pressing and quasi-cold welding composite of manganese oxide and ammonium phosphate particles. Then, it increases the mechanical energy input to construct a highly active precursor, which can increase the reaction interface area and shorten the diffusion distance of manganese and phosphorus components. The defect structure and highly active interface formed by mechanochemical treatment can reduce the kinetic resistance of subsequent pyrophosphate formation and target crystal phase transformation, which is conducive to the formation of manganese ammonium pyrophosphate at relatively low temperatures and reduces the loss of ammonium components and particle sintering caused by high-temperature long-term reaction. By selectively removing zinc, controlling residual carbon, adjusting the average valence state of manganese, and controlling the oxygen partial pressure during heat treatment, the formation of zinc phosphate, manganese oxides, and non-target manganese phosphate impurities can be suppressed, thereby improving the purple hue, dispersibility, and batch stability of the pigment. This invention utilizes manganese resources from waste zinc-manganese battery black powder and phosphorus and ammonium resources from recovered ammonium phosphate salts, reducing the consumption of high-purity raw materials and enabling further recovery of zinc leaching solution, ammonium phosphate purification mother liquor and ammonia-containing tail gas. This invention focuses on solid-phase or near-dry mechanochemical treatment, eliminating the need to convert all manganese elements into a high-concentration manganese-containing solution first. This reduces the multiple leaching, extraction, precipitation, and evaporation steps in traditional wet processes, and features strong raw material adaptability and ease of process scaling. Attached Figure Description

[0022] Figure 1 This is a technical roadmap for the present invention.

[0023] Figure 2 Manganese violet pigment products prepared from waste lithium batteries, where (a) shows the microstructure, and (b), (c), and (d) are the elemental distribution diagrams of manganese, phosphorus, and nitrogen, respectively.

[0024] Figure 3 XRD pattern of manganese violet pigment prepared from waste lithium batteries. Detailed Implementation

[0025] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. The components of the embodiments of the present invention described and shown in the accompanying drawings can generally be arranged and designed in various different configurations.

[0026] A method for preparing manganese violet pigment using waste zinc-manganese battery black powder and recycled ammonium phosphate salt includes the following steps: S0. Waste carbon zinc-manganese batteries and / or waste alkaline zinc-manganese batteries are safely discharged, and then crushed, magnetically separated, air-separated, eddy current separated and screened to separate iron shells, zinc sheets, carbon rods, plastics and paper materials to obtain waste zinc-manganese battery black powder. S1. The waste zinc-manganese battery black powder is subjected to water washing and desalination, physical decarbonization and dezincification treatment to reduce the content of soluble salts, zinc and carbonaceous components, and obtain low zinc, low carbon and manganese rich oxide; wherein, the dezincification treatment adopts ammonia complex leaching, alkaline leaching, selective acid leaching, physical sorting or a combination thereof. Then, the recovered ammonium phosphate salt is purified and acidified for reconstruction. Specifically, the effective phosphorus content and ammonium nitrogen content in the recovered ammonium phosphate salt are detected. The magnesium, calcium, iron, sodium, potassium, and organic impurities are reduced through dissolution, filtration, adsorption for impurity removal, ion exchange, and / or recrystallization. Phosphoric acid and / or recovered phosphoric acid are added to the purified recovered ammonium phosphate salt to achieve the desired molar ratio of effective ammonium to manganese in the final reaction system. 4+The total phosphorus content (P:Mn) is 1.02~1.20:1, and the total phosphorus to manganese molar ratio (P:Mn) is 1.95~2.15:1. After negative pressure concentration and low temperature dehydration, acidified ammonium phosphate composite material is obtained in the form of non-flowing powder, granules or plastic agglomerates.

[0027] In this embodiment, during the purification and acidification reconstruction of the recovered ammonium phosphate salt, the theoretical molar ratio of ammonium, manganese, and phosphorus in the target product NH4MnP2O7 is: n(NH 4+ ):n(Mn):n(P)=1:1:2; In this embodiment, the recovered phosphate ammonium salt provides both ammonium and partial phosphorus sources, and phosphoric acid and / or recovered phosphoric acid are used to supplement total phosphorus and adjust acidity. To address fluctuations in the available phosphorus, ammonium nitrogen, and impurity content of the recovered phosphate ammonium salt from different sources, the available phosphorus and ammonium nitrogen contents were measured separately. The phosphorus-manganese ratio and ammonium-manganese ratio in the system were adjusted by molar amount, rather than being directly fed according to the original mass of the recovered phosphate ammonium salt.

[0028] The recovered ammonium phosphate salts are acidified to form an acidified ammonium phosphate composite containing diammonium dihydrogen phosphate, phosphoric acid, diammonium hydrogen phosphate acidification products, and a small amount of condensed phosphate. This composite has the combined properties of acid phosphate supply, ammonium ion supply, and interfacial plasticity. Under mechanical force, it can be more uniformly embedded on the surface of defective manganese-rich oxides, reducing local acid enrichment, particle agglomeration, and uneven phosphorus-manganese ratio caused by the direct addition of liquid phosphoric acid.

[0029] S2. Conduct the first stage of mechanochemical lattice defect construction. Place the low-zinc, low-carbon manganese-rich oxides separately in a high-energy mechanochemical treatment device. Through the impact, shearing, friction and extrusion of grinding balls or grinding media, the manganese-rich oxide particles are broken, and the MnO6 coordination structure is lattice distorted, forming one or more of the following: dislocations, stacking faults, grain boundaries, oxygen vacancies, low-coordination manganese sites and Mn-O bond breaking sites, to obtain defective manganese-rich oxides.

[0030] S3. Perform the second stage of mechanochemical interface coupling. Add the acidified ammonium phosphate composite material to the defective manganese-rich oxide in 2 to 5 batches. After each batch is added, continue to perform mechanochemical treatment so that the acidified ammonium phosphate composite material undergoes local viscoplastic flow, embedding and interfacial bonding under mechanical impact, shearing and compaction. It also forms a Mn-OP interface bond with the newly formed surface of the defective manganese-rich oxide to obtain the manganese-phosphorus-ammonium mechanochemical coupling precursor. The moisture content of the second stage mechanochemical treatment system is not higher than 5 wt.%, and the material does not form a free-flowing slurry.

[0031] The waste zinc-manganese battery black powder, after desalting, decarbonizing, and dezincifying, yields manganese-rich oxides composed of MnO2, MnOOH, Mn2O3, a small amount of Mn3O4, and amorphous manganese oxides. The different phases exhibit variations in manganese valence state, Mn-O coordination structure, and thermal reactivity. While conventional mixing or ultrafine grinding can reduce particle size, it is difficult to fully disrupt the manganese oxide lattice, and subsequent phosphorylation reactions are easily limited by the surface phosphate layer and the unreacted manganese oxide core.

[0032] In this embodiment, a first-stage high-energy mechanical activation is performed on low-zinc, low-carbon, manganese-rich oxides without the addition of ammonium phosphate salts. The impact, shearing, friction, and extrusion of the grinding balls cause particle breakage and induce distortion of the MnO6 coordination structure, forming dislocations, stacking faults, grain boundaries, oxygen vacancies, and low-coordination manganese sites. This process not only manifests as particle refinement but also as broadening of manganese oxide X-ray diffraction peaks, increased lattice microstrain, shift of Mn-O vibrational peaks, increased defect oxygen ratio, and adjustment of the average valence state of manganese, thereby forming a new surface with high interfacial reactivity.

[0033] Next, after the first stage of treatment, the acidified ammonium phosphate composite was added in batches to the defect-activated manganese-rich oxides, and the second stage of mechanochemical treatment continued. Batch addition reduces the coating of the soft ammonium phosphate salts on the manganese-rich oxides and grinding balls in the early stages of ball milling, allowing acidic phosphate ions to preferentially contact the newly formed surface and lattice defect sites. Under instantaneous high pressure, shear, and localized temperature rise, the acidified ammonium phosphate composite softens, compacts, and undergoes localized viscoplastic flow, embedding itself into the cracks, channels, and grain boundaries of the manganese-rich oxides, forming a dense composite interface that is difficult to separate by simple sieving or pneumatic classification.

[0034] The term "quasi-cold welding" refers to the embedding, compaction, and interfacial bonding of acidified ammonium phosphate composites under mechanical force, rather than macroscopic plastic cold welding between metal powders. At the composite interface, acidic phosphate ions can interfacially bond with low-coordination manganese sites to form an Mn-OP bridging structure.

[0035] The precursors obtained after mechanochemical treatment mainly exhibit a short-range ordered and long-range disordered manganese-oxygen-phosphorus complex structure, which may contain Mn-OP bridging structures, amorphous manganese phosphates, acid manganese phosphates, and condensed phosphate precursor structures.

[0036] S4. Perform mechanochemical-low-temperature pyrophosphorylation coupling, directly subjecting the manganese-phosphorus-ammonium mechanochemical coupling precursor to segmented heat treatment; the segmented heat treatment sequentially includes low-temperature dehydration at 100~150℃, interfacial condensation at 190~240℃, and low-temperature crystallization at 260~310℃, causing orthophosphate and acid phosphate to dehydrate and condense to form pyrophosphate, and using the Mn-OP interface formed in the mechanochemical stage as the reaction and nucleation site to generate a crude manganese violet pigment product with NH4MnP2O7 as the main phase.

[0037] In conventional mixtures, the heating process involves sequential softening of ammonium phosphate salts, phosphate migration, lattice disruption of manganese oxides, Mn-OP bond formation, phosphate condensation, and nucleation of the target crystal phase. The reaction is easily limited by solid-phase diffusion and interface passivation. In this embodiment, a highly active precursor with abundant lattice defects, uniform manganese-phosphorus distribution, and Mn-OP interfacial bonding is pre-formed through staged mechanochemical treatment, enabling subsequent pyrophosphorylation to be primarily completed through interfacial reactions and short-range diffusion.

[0038] The precursor is subjected to segmented heat treatment: free water, adsorbed water and weakly bound water are removed at 100~150℃; the dehydration and condensation of phosphate groups are promoted at 190~240℃ to form POP bonds; and pyrophosphate, ammonium and trivalent manganese undergo lattice rearrangement at 260~310℃ to form NH4MnP2O7 crystal nuclei and continue to grow.

[0039] Through mechanochemical preactivation and interfacial coupling, phosphate ions can undergo dehydration condensation and crystal nucleation near defective manganese sites without long-distance migration, thereby reducing the crystallization temperature of manganese violet pigment, reducing rapid decomposition of ammonium ions, precursor bubbling, local sintering and unreacted manganese oxide cores, and improving the phase formation rate and product uniformity of NH4MnP2O7.

[0040] S5. Perform acid gradient water washing and low-temperature drying. The crude manganese violet pigment product is washed with phosphoric acidified water with a pH of 2.5~4.5 to remove residual ammonium phosphate salts and soluble zinc, magnesium, calcium, sodium and potassium salts. After solid-liquid separation, vacuum low-temperature drying and grinding or air jet milling, the manganese violet pigment product is obtained.

[0041] Manganese violet pigment is an ammonium pyrophosphate pigment. Under alkaline media or high-temperature water washing conditions, the particle surface may undergo localized hydrolysis, ammonium ion exchange, or fine particle colloidation. In this embodiment, phosphoric acidified water with a pH of 2.5~4.5 is used for gradient washing: the first stage removes soluble ammonium phosphate, sodium, potassium, and chloride salts adsorbed on the particle surface at 15~30℃; the second stage further removes residual zinc, magnesium, calcium, and excess phosphate salts in the pores at 35~55℃.

[0042] A weakly acidic washing environment can reduce surface hydrolysis and ammonium ion loss in manganese violet pigment; a gradient washing method, starting with low temperature and then medium temperature, can achieve a balance between the removal rate of soluble impurities and the retention rate of fine manganese violet particles. Vacuum drying of the washed wet material at 50~100℃ can reduce ammonium ion decomposition, soluble salt migration, and hard agglomeration of particles; after grinding or airflow deagglomeration, manganese violet pigment with a narrow particle size distribution and good dispersibility is obtained.

[0043] The following detailed description, in conjunction with the accompanying drawings and small-scale experimental examples, will be provided. Example

[0044] like Figure 1 As shown, a method for preparing manganese violet pigment using waste zinc-manganese battery black powder and recycled ammonium phosphate salt includes the following steps: S0. Safe Discharge: Collect waste No. 5 alkaline zinc-manganese batteries and waste No. 5 carbon zinc-manganese batteries, and discard those that are bulging, severely damaged, leaking, poorly labeled, or mixed with nickel-cadmium, nickel-metal hydride, or lithium-ion batteries. Connect the screened waste zinc-manganese batteries to an adjustable resistive load discharge cabinet and discharge them at an equivalent discharge rate of 0.1~0.3C. Use a multimeter to measure the battery terminal voltage. When the terminal voltage of a single battery drops to no higher than 0.2V, let it stand for another 2 hours and remeasure the voltage. Batteries whose voltage rebounds to above 0.2V are connected to the load for discharge again until the safety dismantling requirements are met.

[0045] S0-1. Physical Pretreatment: a. Crushing: Place the discharged waste zinc-manganese batteries in a closed negative pressure crushing device and crush them to a particle size of no more than 10mm using a two-stage crushing method; b. Magnetic Separation: Use a magnetic separator with a magnetic field strength of 0.2~0.5T to separate iron shells, iron filings and other magnetic materials; c. Eddy Current Separation: Separate sheet zinc shells, copper caps and other non-ferrous metal materials; d. Air Separation: Remove plastic, paper insulation layers and lightweight sealing materials under wind speed of 6~10m / s; e. Screening: Separate black powder through an 80~200 mesh vibrating screen. Carbon rods and insufficiently dissociated particles on the screen are returned to the crushing equipment, and the undersize material is used as waste zinc-manganese battery black powder (Mn 39.8wt.%, Zn 15.6wt.%, total carbon 12.4wt.%, Fe 1.2wt.%, etc.).

[0046] S1. Desalination, decarbonization, and dezincification pretreatment: Take 500g of waste zinc-manganese battery black powder obtained in step S0-1, add it to 3000mL of deionized water at a solid-liquid ratio of 1:6, stir for 15 minutes at 25℃ and 300rpm, let stand for 5 minutes, and then filter. Repeat the washing process twice to remove ammonium chloride, zinc chloride, potassium hydroxide, potassium carbonate, and other soluble salts.

[0047] The washed filter residue was added to the flotation tank, and water was added at a solid-liquid ratio of 1:8 to adjust the slurry pH to 7-8. Kerosene was used as the collector for the carbonaceous components, added at 0.03 wt.% of the black powder mass; methyl isobutyl methanol was used as the frother, added at 0.008 wt.% of the black powder mass. The aeration rate was 0.15 m³ / min. 3 / (m 2 ·min), under a stirring speed of 1200 rpm, flotation was carried out for 8 minutes, and graphite and acetylene black in the foam layer were collected. The bottom material of the tank was desalted and decarbonized manganese-rich black powder.

[0048] In this embodiment, selective leaching with ammoniacal ammonium carbonate is used as the zinc removal method. An ammoniacal ammonium carbonate solution containing 2 mol / L ammonium carbonate and 4 mol / L free ammonia is prepared. Desalted and decarbonated manganese-rich black powder is added to the ammoniacal ammonium carbonate solution at a solid-liquid ratio of 1:10, and leaching is performed at 40°C and 250 rpm for 30 minutes. After filtration, the filter residue is added to fresh ammoniacal ammonium carbonate solution at a solid-liquid ratio of 1:8, and a second leaching is performed at 40°C for 20 minutes.

[0049] The two leachates were combined, and the filter residue was quickly washed once with dilute ammonia water containing 0.2 mol / L ammonium carbonate, followed by washing with deionized water until the Zn concentration in the washing solution was below 50 mg / L. The zinc-containing ammonia leachate was treated by ammonia stripping, carbonation, and precipitation to recover basic zinc carbonate. The recovered ammonia was absorbed and returned to the zinc removal step.

[0050] The dezincified manganese-rich solid phase was pre-dried under vacuum at 80℃, and then placed in an air atmosphere and heated to 360~400℃ at 3℃ / min, and held for 30~60 minutes to remove residual carbon and organic matter, to obtain low-zinc, low-carbon manganese-rich oxide (mass 295.8g, of which Mn 63.4wt.%, Zn 0.65wt.%, total carbon 0.58wt.%).

[0051] Purification and Acidification Reconstruction of Recovered Phosphate Ammonium Salt: The recovered phosphate ammonium salt used in this embodiment is derived from a mixed phosphate ammonium salt (91.8 wt.% ammonium dihydrogen phosphate and 3.2 wt.% diammonium hydrogen phosphate) obtained by concentrating and crystallizing phosphorus and ammonia-containing industrial wastewater. The recovered phosphate ammonium salt was added to deionized water at 60°C at a solid-liquid ratio of 1:2 and stirred for 30 minutes to dissolve. 1 g / L of powdered activated carbon was added and stirred for another 20 minutes to adsorb organic matter and colored impurities. After filtration and cation exchange treatment to reduce the content of Mg, Ca, and Fe, the salt was concentrated and crystallized under 60-75°C and negative pressure to obtain purified recovered phosphate ammonium salt.

[0052] Based on the Mn content in low-zinc, low-carbon, manganese-rich oxides, 295.8g of manganese-rich oxides contains approximately 187.5g of Mn, or about 3.41mol. According to the final reaction system, NH... 4+ The ingredients were mixed with Mn = 1.08:1 and P:Mn = 2.08:1.

[0053] Weigh out the purified and recovered ammonium phosphate salt based on the effective ammonium dihydrogen phosphate, so that it provides about 3.68 mol of effective ammonium ions and 3.68 mol of phosphorus; then add phosphoric acid with a mass concentration of 85 wt.% to make the total phosphorus content of the system reach about 7.09 mol.

[0054] The purified and recovered ammonium phosphate salt is added to a vacuum kneader resistant to phosphoric acid corrosion. Phosphoric acid is sprayed in under stirring conditions of 40-60 rpm for 20-40 minutes. After the phosphoric acid is added, the mixture is kneaded and concentrated for 30-120 minutes at 60-90℃ and a vacuum of -0.06MPa to -0.09MPa, so that the material is transformed into powder, granules, or plastic agglomerates that do not form free-flowing slurries.

[0055] The resulting acidified ammonium phosphate composite contains ammonium dihydrogen phosphate, phosphoric acid and a small amount of condensed phosphate, and simultaneously provides the ammonium and phosphorus sources required to form the manganese purple lattice.

[0056] S2. First-stage mechanochemical lattice defect construction: 295.8g of low-zinc, low-carbon, manganese-rich oxide obtained in step S1 was added separately to a planetary ball mill. A zirconia ball mill jar and zirconia grinding balls were used, with a ball particle size ratio of 5mm diameter: 10mm diameter = 2:1. The ball-to-material ratio was controlled at 12:1, the ball milling speed was 550rpm, and the ball milling time was 45 minutes. Jacketed cooling and intermittent ball milling were used, with a 5-minute cooling period after every 15 minutes of continuous ball milling to ensure that the material temperature did not exceed 60℃.

[0057] In the first stage, no recycled ammonium phosphate salts, phosphoric acid, or acidified ammonium phosphate composites are added to avoid the soft ammonium phosphate components prematurely coating the grinding balls and manganese-rich oxides, thus ensuring that the grinding balls can input sufficient mechanical energy to the manganese oxides.

[0058] S3. Second stage of mechanochemical interface coupling: The acidified ammonium phosphate composite material obtained in step S1 is added to a ball mill jar containing defective manganese-rich oxide in three batches; The first batch of 30% of the total mass of acidified ammonium phosphate composite material was added and ball-milled for 30 minutes at 420 rpm. The second batch consists of 30% of the total mass of acidified ammonium phosphate composite material, and ball milling continues for 30 minutes. The remaining 40% of the acidified ammonium phosphate composite material was added in the third batch, and ball milling continued for 60 minutes.

[0059] The second-stage mechanochemical treatment uses a ball-to-material ratio of 8:1 (calculated based on total material mass), a ball mill speed of 420 rpm, and a total milling time of 120 minutes to form a manganese-phosphorus-ammonium mechanochemically coupled precursor. Jacketed cooling and intermittent ball milling are used to control the material temperature to not exceed 70℃.

[0060] S4. Mechanochemical-low-temperature pyrophosphorylation coupling: The manganese-phosphorus-ammonium mechanochemical coupling precursor obtained in step S3 is directly subjected to heat treatment after the mechanochemical treatment is completed. The mechatronic coupling precursor was spread evenly in a phosphoric acid-resistant ceramic reaction dish, with the material layer thickness controlled at 10~25mm, and placed in a programmed temperature rise furnace equipped with a tail gas absorption system for segmented heat treatment according to the following procedure: First stage: Heat to 130℃ at a rate of 2℃ / min and hold for 60 minutes to remove free water and adsorbed water; The second stage involves heating to 225°C at a rate of 1.5°C / min and holding for 60 minutes to promote the dehydration and polycondensation of phosphate groups at the interface and the formation of POP bonds. The third stage involves heating to 290℃ at a rate of 1℃ / min and holding for 150 minutes to allow pyrophosphate, ammonium, and manganese to undergo lattice rearrangement and manganese violet crystal growth at the Mn-OP pre-formation interface.

[0061] After the reaction is complete, the mixture is cooled to below 120°C in the furnace and then transferred to a desiccator to cool to room temperature, yielding the crude manganese violet pigment product.

[0062] S5. Acid gradient water washing and product preparation: The crude manganese violet pigment product is pre-ground to a particle size of less than 500 μm, and then acid gradient water washing is performed as follows; First stage: Add phosphoric acidified water at 25℃ and pH 3 at a solid-liquid ratio of 1:5, stir for 10 minutes to remove residual ammonium phosphate, potassium salt, sodium salt and chloride salt adsorbed on the surface of pigment particles; Second stage: After filtration, add phosphoric acidified water at 45℃ and pH 3.8 at a solid-liquid ratio of 1:4, stir for 15 minutes to further remove residual zinc salts, magnesium salts, calcium salts and excess phosphates from the pores.

[0063] After the second stage of washing, centrifugation was performed, and the filter cake was quickly rinsed with a small amount of deionized water with a pH of 3.5.

[0064] The washed wet manganese violet material was placed in a vacuum drying oven for 12 hours to dehydrate, resulting in loose manganese violet lumps; after being finely ground by an agate grinder, the finished manganese violet pigment was obtained.

[0065] Comparative Example 1 In this comparative example, the difference from Example 1 is that, except for the absence of the first stage of mechanochemical lattice defect construction in step S2 and the second stage of mechanochemical interface coupling in step S3, the other raw material composition, stoichiometry and heat treatment conditions are the same as in Example 1.

[0066] Specifically, the low-zinc, low-carbon manganese-rich oxide was processed using an air jet mill to achieve a D50 of 2.3 μm, similar to the particle size of the defective manganese-rich oxide and the final mechanochemical coupling precursor in Example 1. Subsequently, the air-jet-milled manganese-rich oxide and the acidified ammonium phosphate composite were added to a paddle mixer and mixed at 300 rpm for 2 hours. Then, pyrophosphorication was carried out according to the same segmented heat treatment regime of 130°C, 225°C, and 290°C as in Example 1.

[0067] Comparative Example 2 In this comparative example, the difference from Example 1 is that, except for the addition of low-zinc, low-carbon manganese-rich oxide and all acidified ammonium phosphate composite material to the ball mill jar at one time, the other raw material ratios, total ball milling time, ball milling equipment, grinding ball material and subsequent segmented heat treatment conditions are the same as in Example 1.

[0068] Comparative Example 3 In this comparative example, the difference from Example 1 is that, except for the addition of a solvent remover to the second-stage mechanochemical treatment system to form a free-flowing slurry, the remaining raw material composition and mechanochemical treatment time are the same as in Example 1. The solid content of the liquid-phase ball-milled slurry is controlled at 30 wt.%.

[0069] Comparative Example 4 In this comparative example, the difference from Example 1 is that, except that the segmented low-temperature heat treatment at 130°C, 225°C and 290°C in step S4 is replaced by directly raising the temperature to 360°C and holding it at that temperature for 2 hours, the other steps are the same as in Example 1.

[0070] Table 1 below shows the exemplary quality comparison results of Example 1, commercially available manganese violet pigment, and various comparative examples: Table 1

[0071] Furthermore, the sintering precursors of the original manganese-rich oxide, Comparative Example 1, Comparative Example 2, Comparative Example 3, and Example 1 were compared, and the exemplary results are shown in Table 2 below: Table 2

[0072] Based on Tables 1 and 2, Example 1 is the preferred embodiment of this application; The exemplary pyrophosphorylation initiation temperature of its staged mechanochemically coupled precursor is 258°C, which is 28°C lower than that of the precursor in Comparative Example 1; the main crystallization peak temperature is reduced from 327°C to 296°C. Under low-temperature crystallization conditions of 290℃, the NH4MnP2O7 phase content in the obtained manganese violet pigment reached 96.1 wt.%, which was higher than that of Comparative Example 1, Comparative Example 2 and Comparative Example 3. The ammonium nitrogen content of the product was 5.46 wt.%, which was significantly higher than that of the product in Comparative Example 4; Based on Mn in the waste zinc-manganese battery black powder entering the pretreatment step, the comprehensive manganese recovery rate is, for example, over 85%; based on Zn entering the dezincification step, the zinc removal and recovery rate is, for example, over 95%.

[0073] Analysis of Comparative Example 1 shows that its sample has an exemplary lattice microstrain of 0.25%, which is significantly lower than the 0.74% of the precursor prepared in Example 1; the proportion of XPS defect oxygen-related peaks is 20.1%, which is also lower than the 32.8% of Example 1.

[0074] TG-DSC analysis showed that the pyrophosphorylation initiation temperature of the precursor in Comparative Example 1 was 286°C, and the major crystallization peak temperature was 327°C; while the pyrophosphorylation initiation temperature of Example 1 was 258°C, and the major crystallization peak temperature was 296°C.

[0075] Under the same low-temperature crystallization conditions of 290℃, the NH4MnP2O7 phase content in the product obtained in Comparative Example 1 was 79.2 wt.%, and significant unreacted MnO2 / MnOOH and manganese orthophosphate impurities were still present. The obtained product had an Mn content of 20.3 wt.% and a color of L. ∗ =42、a ∗ =+19.2、b ∗ =−17.1, and the particle size D50 is 4.5±1.0μm.

[0076] In Comparative Example 1, even though the manganese-rich oxide was processed to the same or similar particle size as in Example 1 by ordinary air jet milling, the subsequent reaction was still limited by the destruction of the manganese oxide lattice and solid-phase diffusion because it did not form sufficient lattice distortion, oxygen vacancies and low-coordinated manganese sites, and the acidified ammonium phosphate composite did not form a uniform Mn-OP bonding interface at the defect sites.

[0077] Comparative Example 2 was analyzed, in which all manganese-rich oxide and acidified ammonium phosphate composites were added to the ball mill jar at once and ball-milled together for the same total mechanochemical treatment time as in Example 1. In the initial stage of ball milling, some of the acidified ammonium phosphate composites were observed to adhere to the grinding balls and the wall of the ball mill jar, indicating that the soft ammonium phosphate component provided some buffering against the impact of the grinding balls.

[0078] The precursor obtained in Comparative Example 2 has a D50 of 2.2 μm, which is similar to that of the precursor in Example 1, but its lattice microstrain is 0.44%, which is lower than that of Example 1 (0.74%). The coefficient of variation of Mn and P plane distribution is 17.8%, which is higher than that of Example 1 (8.7%), indicating that the one-time addition caused the acidified ammonium phosphate composite to form a more obvious local enrichment zone.

[0079] TG-DSC analysis showed that the pyrophosphorylation initiation temperature of the precursor in Comparative Example 2 was 275℃, and the major crystallization peak temperature was 315℃. After the same segmented heat treatment, the NH4MnP2O7 phase content in the obtained product was 86.8 wt.%, the Mn content was 20.8 wt.%, and the color was L. ∗ =43.1、a ∗ =+22.1、b ∗ =−20.

[0080] The main reasons why the product in Comparative Example 2 was less effective than that in Example 1 include: First, the soft acidified ammonium phosphate composite material coats part of the grinding balls and manganese oxide-rich particles at the beginning of the ball milling process, thereby reducing the effective impact strength of the grinding balls on the manganese oxides. Second, the manganese oxides were covered by the ammonium phosphate component before they could form enough defect sites, which was not conducive to the continuous lattice distortion of the MnO6 coordination structure. Third, adding it all at once can easily create localized areas of enrichment in ammonium phosphate and manganese oxides.

[0081] Analysis of Comparative Example 3 shows that during the liquid-phase ball milling process, water molecules form a hydration layer on the surface of manganese oxide and phosphate, which buffers the impact of the grinding balls and the solid-solid contact. In the liquid-phase system, the acidified ammonium phosphate composite material mainly exists in the form of hydrated ions or dissolved components, making it difficult to achieve the localized viscoplastic pressing and quasi-cold welding-type embedding described in Example 1.

[0082] After drying, the liquid-phase ball-milled precursor had a D50 of 2.1 μm, a lattice microstrain of 0.31%, an XPS defect oxygen-related peak ratio of 22.4%, and a Mn and P surface distribution variation coefficient of 23.1%. Despite its smaller particle size, the degree of lattice defects and interface coupling was significantly lower than that of the precursor in Example 1.

[0083] After undergoing the same segmented low-temperature heat treatment, the NH4MnP2O7 phase content in the product obtained in Comparative Example 3 was 81 wt.%, and the product color was L. ∗ =41.8、a ∗ =+20.0、b ∗ =−17.8.

[0084] The above results indicate that a large amount of liquid water buffers mechanical impact, forms a surface hydration layer, and reduces the degree of direct interfacial compression between defective manganese oxides and acidic phosphate. Therefore, controlling the second-stage mechanochemical system as a dry or near-dry non-flowing system with a water content of no more than 5 wt.% is beneficial for forming the Mn-OP mechanochemical coupling interface.

[0085] Analysis of Comparative Example 4 revealed that during its heat treatment, the precursor exhibited significant bubbling and localized agglomeration, and the ammonia concentration in the tail gas absorbent increased markedly. The NH4MnP2O7 phase content in the product was only 66.9 wt.%, and impurities of manganese pyrophosphate, manganese metaphosphate, and a small amount of divalent manganese phosphate were present. The ammonium nitrogen content in the product decreased to 2.83 wt.%.

[0086] The obtained product had an Mn content of 22.9 wt.%. Its apparent Mn mass fraction increased due to the loss of ammonium and volatile components, but its color decreased by L. ∗ =39.1、a ∗ =+14.6、b ∗ =−11.2, the particle size D50 increased to 6.0±1.4μm, and the powder was dark purple-brown.

[0087] The main reasons why the test results of Comparative Example 4 were lower than those of Example 1 include: First, if the phosphate groups are not fully and uniformly condensed before entering a high temperature, a dense phosphate layer is easily formed on the particle surface. Second, the higher temperature leads to the rapid decomposition of the phosphorus ammonium component and the ammonium ions in the manganese purple lattice; Third, localized high temperatures promote particle sintering and hard agglomeration, resulting in increased particle size and reduced dispersibility.

[0088] Therefore, the mechanochemical coupling precursor of the present invention needs to be matched with low-temperature dehydration at 100~150℃, interfacial polycondensation at 190~240℃ and low-temperature crystallization at 260~310℃ in order to take into account pyrophosphate formation, manganese valence state adjustment and ammonium ion retention.

[0089] Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing manganese violet pigment using waste zinc-manganese battery black powder and recycled ammonium phosphate, characterized in that, Includes the following steps: S1. Pre-treat the waste zinc-manganese battery black powder and the recovered ammonium phosphate salt separately to obtain a composite material of manganese-rich oxide and acidified ammonium phosphate; S2. The manganese-rich oxide is subjected to a first mechanochemical treatment alone to obtain a defective manganese-rich oxide; S3. The acidified ammonium phosphate composite is added to the defective manganese-rich oxide in batches, and a second mechanochemical treatment is carried out under the condition that the moisture content is not higher than 5 wt.% to obtain the manganese-phosphorus-ammonium mechanochemical coupling precursor. S4. The manganese-phosphorus-ammonium mechanochemical coupling precursor is directly subjected to segmented heat treatment, wherein the segmented heat treatment includes dehydration, interfacial polycondensation and crystallization in sequence to obtain crude manganese violet pigment product. S5. The crude manganese violet pigment product is washed and dried to obtain the manganese violet pigment product.

2. The method for preparing manganese violet pigment using waste zinc-manganese battery black powder and recycled ammonium phosphate salt according to claim 1, characterized in that, The preprocessing described in step S1 includes: The waste zinc-manganese battery black powder is subjected to desalination, decarbonization and dezincification treatment; Purification of the recovered ammonium phosphate salt and acidification reconstruction by adding phosphoric acid and / or recovering phosphoric acid.

3. The method for preparing manganese violet pigment using waste zinc-manganese battery black powder and recycled ammonium phosphate salt according to claim 2, characterized in that, The zinc removal process employs at least one of the following methods: ammonia complex leaching, alkaline leaching, selective acid leaching, or physical sorting.

4. The method for preparing manganese violet pigment using waste zinc-manganese battery black powder and recycled ammonium phosphate salt according to claim 2, characterized in that, The purification includes dissolution, filtration, adsorption, ion exchange, and / or recrystallization; the acidification and reconstruction adjusts the molar ratio of effective ammonium ions to manganese in the acidified ammonium phosphate composite material (NH4+). 4+ The ratio of total phosphorus to manganese (P:Mn) is 1.02 to 1.20:1, and the molar ratio of total phosphorus to manganese (P:Mn) is 1.95 to 2.15:

1.

5. A method for preparing manganese violet pigment using waste zinc-manganese battery black powder and recycled ammonium phosphate salt according to claim 1, characterized in that, In step S2, the first mechanical chemical treatment is performed by ball milling, with a ball-to-material ratio of 8:1 to 15:1, a ball milling speed of 450 to 650 rpm, a ball milling time of 20 to 90 minutes, and a material temperature not exceeding 80°C.

6. The method for preparing manganese violet pigment using waste zinc-manganese battery black powder and recycled ammonium phosphate salt according to claim 1, characterized in that, The acidified ammonium phosphate composite material described in S3 is added in 2 to 5 batches, with each batch accounting for 20 to 50% of the total mass of the acidified ammonium phosphate composite material. After each batch is added, mechanical and chemical treatment is carried out for 10 to 45 minutes, and mechanical and chemical treatment is continued for 30 to 120 minutes after all batches are added.

7. The method for preparing manganese violet pigment using waste zinc-manganese battery black powder and recycled ammonium phosphate salt according to claim 1, characterized in that, The dehydration temperature in step S4 is 100~150℃, the interfacial condensation temperature is 190~240℃, and the crystallization temperature is 260~310℃.

8. The method for preparing manganese violet pigment using waste zinc-manganese battery black powder and recycled ammonium phosphate salt according to claim 7, characterized in that, The segmented heat treatment process is as follows: heat up to 120-140℃ at 1-3℃ / min and hold for 30-90 minutes; heat up to 210-235℃ at 0.5-2℃ / min and hold for 40-120 minutes; heat up to 275-305℃ at 0.5-1.5℃ / min and hold for 60-240 minutes.

9. The method for preparing manganese violet pigment using waste zinc-manganese battery black powder and recycled ammonium phosphate salt according to claim 1, characterized in that, The washing described in step S5 uses phosphoric acidified water with a pH of 2.5 to 4.5, and the washing includes a first-stage washing at 15 to 30°C and a second-stage washing at 35 to 55°C.

10. A method for preparing manganese violet pigment using waste zinc-manganese battery black powder and recycled ammonium phosphate salt according to claim 1, characterized in that, The drying process described in step S5 is vacuum drying at 50~100℃.

Citation Information

Patent Citations

  • Recycling method of waste zinc-manganese cells

    CN104183856A

  • Method for recovering highly pure manganese dioxide from waste manganese dry batteries, and use of highly pure manganese dioxide

    CN106241880A